Dampak Pendapatan Asli Daerah, Dana Perimbangan dan Produk Domestik Regional Bruto Terhadap Indeks Pembangunan Manusia di Kabupaten Sleman Provinsi Daerah Istimewa Yogyakarta - Nuralam Nuralam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the impact of Regional Original Revenue (PAD), Balancing Funds (DP) consisting of the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH), as well as the Gross Regional Domestic Product (GRDP) on the Human Development Index (HDI). The research was conducted using a quantitative descriptive method aimed at explaining empirical phenomena supported by patterns of relationships among variables, characteristics, and statistical data. Secondary data in the form of time series data over 15 years (2010–2024) were analyzed using multiple linear regression.The results of the statistical analysis show that PAD and DP each have no positive and significant effect on HDI when tested partially. Meanwhile, GRDP has a positive and significant partial effect on HDI. However, simultaneously, the variables PAD (X1), DP (X2), and GRDP (X3), based on the F-test hypothesis, have a positive and significant effect on HDI. In other words, these three variables, both directly and indirectly, contribute jointly to the achievement of the HDI score in Sleman Regency during the study period. In 2024, Sleman’s HDI reached 84.91, classified as “Very High,” surpassing the HDI of Yogyakarta Special Region Province in 2024, which was 81.62 (“Very High”), and the national HDI of 75.02 (“High”), an achievement truly worthy of appreciation.